Student Perceptions of Influences on Career and Educational Decision-Making - Abernathy, Thomas; Davis, William (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper reports on a survey of 2,144 junior and senior secondary school student which examined who it was that they see as having influenced their decisions about an education and career following high school. The results demonstrate that the influence of various sources differs by both the age and sex of the students. On the basis of these findings suggestions are made as to ways in which counsellors might make more effective use of their time and energy.